To solve the inequality \( 5(2k - 3) \geq -3(4 - 3k) \), we will proceed with the following steps:
-
Distribute both sides of the inequality:
\[ 5(2k) - 5(3) \geq -3(4) + 3(3k) \] This simplifies to: \[ 10k - 15 \geq -12 + 9k \]
-
Next, we want to isolate \( k \). First, we'll get all terms containing \( k \) on one side and constant terms on the other side. Subtract \( 9k \) from both sides:
\[ 10k - 9k - 15 \geq -12 \] Which simplifies to: \[ k - 15 \geq -12 \]
-
Now, we will add 15 to both sides:
\[ k \geq -12 + 15 \] This means: \[ k \geq 3 \]
Thus, the solution to the inequality is \( k \geq 3 \).
So, \( k \geq \textbf{3} \).